SYMBOLISM AND METAPHOR IN DEPICTING HUMAN-AI RELATIONSHIPS IN KLARA AND THE SUN - Toirova Nargiza Isakovna; Abdurakhmonova Makhfiratkhon (TADQIQOTLAR, 2025)
Kazuo  Ishiguro’s  Klara  and  the  Sun  explores  the  intersection  of  artificial intelligence (AI) and human emotions, using powerful symbols and metaphors to delve into  themes  of  hope,  fragility,  and  social  alienation.  The  novel's  central  character, Klara,  an  AI,  embodies  innocence  and  emotional  growth  as  she  navigates  human relationships and struggles to understand the complexities of human existence. Key symbols, such as the Sun, the store window, and the barn, illustrate the limitations and possibilities of AI while also highlighting the fragility of human life. By analyzing these symbols and metaphors, this paper examines how Ishiguro uses language and narrative style to convey deep insights into human nature and the boundaries between technology and emotion.